NATED vs NSC - Essack, SY (South African Journal of Higher Education, 2016)
The challenge of translating equity of access into equity of outcome with students from a differentially resourced secondary education system which may have advantaged or disadvantaged them in demonstrating their academic ability in the conventional matriculation/national senior certificate (NSC) examinations necessitated that Universities undertake a review of selection and admissions criteria within the “achievement vs. aptitude” as well as the “NATED vs. NCS” discourses. The Faculty of Health Sciences conducted a longitudinal cohort study correlating matriculation/NSC scores, composite and component Alternative Admissions Research Project (AARP) scores and Standardized Assessment Test for Access and Placement (SATAP) English for Academic Purposes scores with average first year performance of all first entry students admitted into programmes offered in the Faculty of Health Sciences in 2008 (matriculants of the NATED curriculum) and 2009 (NSC holders of the OBE curriculum). Results allow the Faculty to confidently use NSC scores as the primary selection tool for students who have received quality secondary education and students whose first language is English. The RT and PTEEP as well as composite AARP scores may be used to inform selection in the L2 and AA cohorts respectively noting that the AARP has since been replaced by the National Benchmark Test (NBT) which consists of commensurate components; thereby addressing equity and redress imperatives while ensuring throughput and success. Keywords: selection, aptitude, NATED, OBE, NSC